A new cathode for solid oxide fuel cells capable of in situ electrochemical regeneration - Zhou, W.; Shao, Zongping; Liang, F.; Chen, Z.; Zhu, Z.; Jin, W.; Xu, N. (2011)
As highly efficient energy conversion devices with the capability for power/heat co-generation and fuel flexibility, solid-oxide fuel cells (SOFCs) have received considerable attention recently as a keystone of the future energy economy. Nowadays, lack of a proper cathode with high performance at intermediate temperature (IT) has become the main obstacle in realizing this fascinating technology. Here we present (La0.8Sr0.2) 0.95Ag0.05MnO3-d as a novel CO 2 tolerant cathode of IT-SOFCs, which shows silver intercalation/de-intercalation capability. Under cathodic polarization, silver can be extracted from perovskite lattice to form a 5-15 nm silver modified A-site cation deficient (La0.8Sr0.2) 0.95MnO3-d electrode with superior electrocatalytic activity and improved stability. Any performance degradation due to silver sintering can be easily in situ restored by re-intercalating silver into the perovskite lattice under anodic polarization. Through electrochemically adjusting the oxidation state and location of silver, we introduce a way for the development of high-performance silver-modified cathode for IT-SOFCs, which may contribute significantly to a sustainable future. © 2011 The Royal Society of Chemistry.